Comparative and Phylogenetic Analyses of the Complete Chloroplast Genomes of Three Arcto-Tertiary Relicts: Camptotheca acuminata, Davidia involucrata, and Nyssa sinensis - Yang, Zhenyan; Ji, Yunheng (Frontiers in Plant Science, 2017)
The Arcto-Tertiary relict genera, Camptotheca, Davidia and Nyssa represent deep lineages in the asterid order Cornales. Recent phylogenetic studies suggested that these genera should be placed in a newly circumscribed family, Nyssaceae. However, because these analyses were based upon a few genes, it is prudent and necessary to examine further evidence before adopting this taxonomic treatment. In this study, we determined the complete chloroplast (cp) genomes of Camptotheca acuminata, Davidia involucrata, and Nyssa sinensis. Their cp genomes ranged from 156672 to 158409 base pairs, which included 115 genes, and their genome features were highly similar to those of other species within the order Cornales. The phylogenetic relationships among the genera Camptotheca, Davidia, Nyssa, and 23 related taxa in the asterids were analyzed based on 73 protein-coding genes from the cp genomes. All of the previously recognized major clades (namely Cornales, Ericales, Campanulids, and Lamiids) in the asterids, as well as their relationships, were recovered with robust support. A clade including the genera Davidia, Nyssa, Camptotheca, and Diplopanax, was resolved as a well-supported monophyletic group, which was fully separated from the family Cornaceae by the family Hydrangeaceae. Our results provide novel evidence to support the acceptance of the family Nyssaceae outlined by the updated Angiosperm Phylogeny Group.